ULTRASOUND-ENZYME ASSISTED EXTRACTION OF POLYPHENOL AND AMYLASE ENZYME FROM VIETNAMESE RAMIE LEAVES: PREDICTIVE MODELING DEVELOPMENT AND OPTIMIZATION STUDY - Loan, Le Thi Kim; Vinh, Bui The; Van Tai, Ngo (My University, 2024)
Ramie leaves are rich in antioxidant polyphenols and amylase enzyme, which could be a good source for food applications. This study investigated the impact of combined ultrasound-enzyme treatment (U-EAT), including ultrasound intensity (10-30%), content of Viscozyme L. enzyme addition (0.5-1%) and extraction time (5-15 min) on polyphenol recovery, antioxidant activity, and amylase activity. The result revealed that U-EAT could enhance the efficiency of extraction, with a significantly higher yield of bioactive compounds and antioxidant capacity, and amylase enzyme activity compared to an untreated sample. Multiple regression analysis was applied to predict the efficacy of extraction through the values of total phenolic content, antioxidant activity and enzyme activity. The established models shown high accuracy in predicting the effect of the extracted conditions on the yield of the extraction of antioxidant and enzyme amylase. It was found that the maximum yield of extraction could be obtained when the operation conditions were ultrasound intensity of 26.5%, enzyme concentration of 0.87% and extraction time of 10.88 min. Under these optimal conditions, the highest values were found (TPC of 99.047 mgGAE/100 g, antioxidant activity of 65.02% and amylase activity of 45.36 U/mL). In summary, the findings indicate that the utilization of ultrasound combined with the enzymatic extraction process of polyphenol and amylase enzyme from ramie leaves holds potential for enhancing both the extraction yield and bioactivity of the extract. Further study should be concerned with the process of producing food ingredients or products from this extract.
Keywords: amylase; extraction; polyphenol; ramie leaves; sustainable technology